Abnormally Normal

Calculus Level 3

Consider the graph plotted by the equation

k x + y k + x x = x k + k y + y y k^x+y^k+x^x=x^k+k^y+y^y

where x > 0 x>0 , y > 0 y>0 , and k R + k \in \mathbb{R^+} is a constant.

Let G k , t G_{k,t} be the gradient of the normal to a curve of the graph at the point ( t , t ) (t,t) where t Z + t \in \mathbb{Z^+} , t k t \geq k is a real positive integer. Determine the value of

k = 2 2016 ( t = k k + 2015 G k , t ) \prod_{k=2}^{2016} \left( \prod_{t=k}^{k+2015} G_{k,t} \right)


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Wee Xian Bin
Aug 13, 2016

Implicit differentiation of k x + y k + x x = x k + k y + y y k^x+y^k+x^x=x^k+k^y+y^y gives ( k x ) ( ln k ) + ( k ) ( y k 1 ) ( d y d x ) + ( x x ) ( ln x + 1 ) = ( k ) ( x k 1 ) + ( k y ) ( ln k ) ( d y d x ) + ( y y ) ( ln y + 1 ) ( d y d x ) (k^x)(\ln{k}) + (k)(y^{k-1})\left(\frac{dy}{dx}\right) + (x^x)(\ln{x}+1) = (k)(x^{k-1}) + (k^y)(\ln{k})\left(\frac{dy}{dx}\right) + (y^y)(\ln{y}+1)\left(\frac{dy}{dx}\right) ( k ) ( y k 1 ) ( d y d x ) ( k y ) ( ln k ) ( d y d x ) ( y y ) ( ln y + 1 ) ( d y d x ) = ( k ) ( x k 1 ) ( k x ) ( ln k ) ( x x ) ( ln x + 1 ) (k)(y^{k-1})\left(\frac{dy}{dx}\right) - (k^y)(\ln{k})\left(\frac{dy}{dx}\right) - (y^y)(\ln{y}+1)\left(\frac{dy}{dx}\right) = (k)(x^{k-1}) - (k^x)(\ln{k}) - (x^x)(\ln{x}+1) ( d y d x ) ( ( k ) ( y k 1 ) ( k y ) ( ln k ) ( y y ) ( ln y + 1 ) ) = ( k ) ( x k 1 ) ( k x ) ( ln k ) ( x x ) ( ln x + 1 ) \left(\frac{dy}{dx}\right) \left((k)(y^{k-1}) - (k^y)(\ln{k}) - (y^y)(\ln{y}+1)\right) = (k)(x^{k-1}) - (k^x)(\ln{k}) - (x^x)(\ln{x}+1) d y d x = ( k ) ( x k 1 ) ( k x ) ( ln k ) ( x x ) ( ln x + 1 ) ( k ) ( y k 1 ) ( k y ) ( ln k ) ( y y ) ( ln y + 1 ) \frac{dy}{dx} = \frac{(k)(x^{k-1}) - (k^x)(\ln{k}) - (x^x)(\ln{x}+1)}{(k)(y^{k-1}) - (k^y)(\ln{k}) - (y^y)(\ln{y}+1)} For constant k k , at every point ( t , t ) (t,t) where t Z + t \in \mathbb{Z^+} , t k t \geq k , d y d x = 1 \frac{dy}{dx}=1 , hence G k , t = 1 G_{k,t}=-1 . Therefore k = 2 2016 ( t = k k + 2015 G k , t ) = 1 \prod_{k=2}^{2016} \left( \prod_{t=k}^{k+2015} G_{k,t} \right) = 1

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...